Association between treatment response and dose of blonanserin transdermal patch in patients with acute schizophrenia: A post hoc cluster analysis based on baseline psychiatric symptoms - Yoshiteru Takekita; Yuji Matsumoto; Takahiro Masuda; Kazumasa Yoshida; Yosuke Koshikawa; Masaki Kato (Neuropsychopharmacology Reports)
Abstract Aim To explore the optimal dose of blonanserin transdermal patch (BNS‐P) based on baseline psychiatric symptomatic characteristics during acute schizophrenia. Methods A post hoc cluster analysis was conducted using data from a 6‐week randomized, double‐blind, placebo‐controlled study of BNS‐P (40 or 80 mg/day) in acute schizophrenia. We classified patients into three clusters based on baseline psychiatric symptoms. Efficacy was assessed using the change from baseline to week 6 in the PANSS total score. Safety was assessed by the incidence of adverse events. Results Among 577 patients, three clusters were identified, characterized by severe psychiatric (Cluster‐S; n = 122), predominant negative (Cluster‐N; n = 191), and predominant positive (Cluster‐P; n = 264) symptoms. In Cluster‐P, both BNS‐P 40 and 80 mg/day reduced PANSS total score significantly more than placebo (p = 0.036, effect size = 0.342; p < 0.001, effect size = 0.687, respectively). In Cluster‐S and ‐N, only BNS‐P 80 mg/day reduced PANSS total score significantly more than placebo (p = 0.045, effect size = 0.497; p = 0.034, effect size = 0.393, respectively). The effect size was greater at 80 mg/day than at 40 mg/day across all clusters. The most common treatment‐emergent adverse events were akathisia and skin‐related adverse events in all clusters. Conclusion BNS‐P exhibited a dose‐dependent antipsychotic effect in all clusters, particularly highlighting its efficacy in patients with predominant positive symptoms, even at lower doses. These findings provide novel and valuable insights for determining BNS‐P dose tailoring to individual symptomatic characteristics in real‐world practice.